2017
DOI: 10.18203/2349-3291.ijcp20171488
|View full text |Cite
|
Sign up to set email alerts
|

Immunization knowledge, attitude and practice among mothers of children from 0 to 5 years

Abstract: Background: Vaccination is one of the most cost-effective child survival interventions which is practiced throughout the world. All countries in the world have an immunization programme to deliver selected vaccines to the targeted beneficiaries, specially focusing on pregnant women, infants and children, who are at a high risk of diseases preventable by vaccines. In India, six vaccines for preventable diseases (VPD) to reduce childhood mortality & morbidity ie. BCG, DPT, OPV, TT was coming into practice in 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Research from India has found variation in immunization coverage (51%-100%) [15][16][17][18][19][20]. The study site, which was an Anganwadi (the current study) as opposed to a hospital [15,[18][19][20] or communitybased study [16,17,19], may have contributed to the difference in immunization coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from India has found variation in immunization coverage (51%-100%) [15][16][17][18][19][20]. The study site, which was an Anganwadi (the current study) as opposed to a hospital [15,[18][19][20] or communitybased study [16,17,19], may have contributed to the difference in immunization coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Research from India has found variation in immunization coverage (51%-100%) [15][16][17][18][19][20]. The study site, which was an Anganwadi (the current study) as opposed to a hospital [15,[18][19][20] or communitybased study [16,17,19], may have contributed to the difference in immunization coverage. It can be said that the percentage of immunization coverage is high in hospital-based studies, which may be because people who visit paediatric clinics or well-baby clinics are the ones who want to get their child immunized, increasing the percentage of immunization coverage.…”
Section: Discussionmentioning
confidence: 99%